Research advances on epigenetic modifications in dendritic cells in allergic rhinitis - Duan, Siyu; Jia, Ziyi; Zheng, Leilei; Wu, Yisha; Xu, Zhihan; Peng, Haiyi; Xue, Jinmei (Frontiers in Immunology, 2025)
Allergic rhinitis (AR), a globally prevalent allergic airway disorder, fundamentally involves CD4+T cell subset imbalance, notably T helper 2 (Th2) hyperpolarization. As critical antigen-presenting cells bridging innate and adaptive immunity, dendritic cells (DCs) contribute to the pathogenesis of AR by presenting antigens, modulating T cell differentiation, and regulating inflammatory responses. Emerging research highlights epigenetic alterations within DCs-encompassing DNA methylation, histone modifications, and non-coding RNAs (ncRNAs)-as central molecular mechanisms governing their function and contributing to AR-related immune dysregulation. DNA methylation dynamically regulates promoter regions, influencing DC migration, maturation, and T cell polarization, while also potentially contributing to transgenerational susceptibility to AR, though evidence in humans remains limited. By altering chromatin structure, histone modifications reprogram gene expression networks. This epigenetic remodeling modulates the transcription of inflammation-associated genes within DCs, thereby influencing the balance between immune tolerance and activation. ncRNAs post-transcriptionally regulate DC developmental trajectories, activation thresholds, and signaling pathways, thus impacting Th1/Th2 immune balance. This study aims to systematically review recent advances in research on epigenetic modifications in DCs, provide an in-depth analysis of their mechanistic role in the immune dysregulation of AR, elucidate the molecular basis of their function as both an “environment-gene bridge” and a “transgenerational inheritance vector”, identify current research limitations, and suggest future directions. The goal is to offer a theoretical framework focused on DC epigenetic regulation for understanding AR pathogenesis and developing novel intervention strategies. Unlike previous reviews on epigenetics in allergic diseases, which broadly discuss various immune cells, this study specifically focuses on DCs. This focus is justified because DCs are pivotal initiators and regulators of type 2 immune responses, and their epigenetic status directly dictates the initiation strength and duration of allergic reactions. Furthermore, we clarify the molecular logic of the dual mechanisms mentioned above: DC epigenetics serves both as a molecular translator converting environmental signals into gene regulatory outcomes and as a mechanism for transmitting allergic susceptibility across generations without altering the DNA sequence. Finally, we analyze the barriers to the clinical translation of DC epigenetics-targeted therapies, thereby offering a new perspective from translational medicine for shifting the treatment paradigm of AR from symptomatic control toward immune remodeling.